A Broad m6A Modification Landscape in Inflammatory Bowel Disease - Nie, Kai; Yi, Jun; Yang, Yuanyuan; Deng, Minzi; Yang, Yan; Wang, Tianyu; Chen, Xuejie; Zhang, Zhaoyu; Wang, Xiaoyan (Frontiers in Cell and Developmental Biology, 2022)
Background and aims: N6-methyladenosine (m6A) is the most common post-transcriptional modification on eukaryotic mRNA, affecting mRNA’s fate. The role of m6A regulation in inflammatory bowel disease is unclear. Here, we investigated the m6A landscape in inflammatory bowel diseases (IBD). Methods: Eleven human IBD microarray datasets were recruited from Gene Expression Omnibus database and 4 selected as discovery cohorts. An RNA-seq dataset from The Inflammatory Bowel Disease Multi'omics Database was used as a validation cohort. m6A regulators were measured in volunteers’ colonic samples. Consensus clustering and immune scoring were used to estimate the characteristics of m6A regulation in IBD. m6A-related characteristics of different sub-phenotypes, sample sources, and biological therapeutic responses were determined using 7 independent datasets. Results: m6A modification involves methyltransferases (writers), demethylases (erasers), and methylation reading protein (readers). A wide interaction exists between m6A regulators and IBD risk genes. The IBD risk loci also could be modified by m6A modifications in the public m6A sequencing data. Further, m6A regulators displayed extensive differential expression in 4 independent discovery cohorts which share common differential genes (IGF2BP2, HNRNPA2B1, ZCCHC4, EIF3I,). In the validated cohort and enrolled volunteers’ colonic biopsy samples, the differential m6A regulators were reconfirmed. Two clusters from consensus clustering exhibits different immune phenotypes. m6A modified positions exist in the core IBD immune cytokines. Another seeven IBD datasets revealed m6A-related differences across clinical phenotypes, biological samples, and therapeutic response subgroups in IBD patients. Conclusion: Regulation of m6A methylation is widely involved in IBD occurrence and development. m6A modifications in risk variants, core cytokines, immune cells, and other proteins may deeply influence the pathophysiology and clinical phenotypes. Further studies are needed to determine its role in IBD.